Multiscale information processing in the immune system - Navarro Quiroz, Roberto; Villarreal Camacho, Jose; Zarate Peñata, Eloina; Bello Lemus, Yesit; López-Fernández, Claudio; Gomez Escorcia, Lorena; Fernández-Ponce, Cecilia; Rebolledo Cobos, Martha; Fandiño Moreno, Jennifer; Fiorillo-Moreno, Ornella; Navarro Quiroz, Elkin (Frontiers in Immunology, 2025)
The immune system is an advanced, multiscale adaptive network capable of processing biological information across molecular, cellular, tissue, and systemic levels, demonstrating remarkable properties such as antifragility and criticality. We propose a unified theoretical framework based on six canonical functions—sensing, coding, decoding, response, feedback, and learning—that act as scale-invariant operational units, integrating molecular precision, collective cellular intelligence, and systemic coordination into coherent adaptive responses. Through this lens, immune function emerges from universal principles of complex network organization, including symmetry breaking, self-organized criticality, modularity, and small-world topology. These insights pave the way toward a predictive immunology grounded in fundamental physical principles, enabling novel computational modeling approaches and facilitating personalized therapeutic interventions that exploit inherent immunological robustness and plasticity.